Antihypertensive therapies in moderate or severe aortic stenosis: a systematic review and meta-analysis. Issue 10 (5th October 2020) - Sen, Jonathan; Chung, Erin; Neil, Christopher; Marwick, Thomas
Abstract : Background: Hypertension confers a poor prognosis in moderate or severe aortic stenosis (AS), however, antihypertensive therapy (AHT) is often not prescribed due to the perceived deleterious effects of vasodilation and negative inotropes. Objective: To assess the efficacy and safety outcomes of AHT in adults with moderate or severe AS. Design: Systematic review and meta-analysis. Data sources: The Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE and grey literature were searched without language restrictions up to 9 September 2019. Study eligibility criteria, appraisal and synthesis methods: Two independent reviewers performed screening, data extraction and risk of bias assessments from a systematic search of observational studies and randomised controlled trials comparing AHT with a placebo or no AHT in adults with moderate or severe AS for any parameter of efficacy and safety outcomes. Conflicts were resolved by the third reviewer. Meta-analysis with pooled effect sizes using random-effects model, were estimated in R . Main outcome measures: Mortality, Left Ventricular (LV) Mass Index, systolic blood pressure, diastolic blood pressure and LV ejection fraction Results: From 3025 publications, 31 studies (26 500 patients) were included in the qualitative synthesis and 24 studies in the meta-analysis. AHT was not associated with mortality when all studies were pooled, but heterogeneity was substantial across studies. The effect size of AHT differed according to drug class. Renin–angiotensin–aldosterone system inhibitors (RAASi) were associated with reduced risk of mortality (Pooled HR 0.58, 95% CI 0.43 to 0.80, p=0.006), The differences in changes of haemodynamic or echocardiographic parameters from baseline with and without AHT did not reach statistical significance. Conclusion: AHT appears safe, is well tolerated. RAASi were associated with clinical benefit in patients with moderate or severe AS.